2013
DOI: 10.1007/s10468-013-9424-0
|View full text |Cite
|
Sign up to set email alerts
|

Algebras Whose Coxeter Polynomials are Products of Cyclotomic Polynomials

Abstract: Abstract. Let A be a finite dimensional algebra over an algebraically closed field k. Assume A is basic connected with n pairwise non-isomorphic simple modules. We consider the Coxeter transformation φ A as the automorphism of the Grothendieck group K 0 (A) induced by the Auslander-Reiten translation τ in the derived category Der(modA) of the module category modA of finite dimensional left A-modules. We say that A is an algebra of cyclotomic type if the characteristic polynomial χ A of φ A is a product of cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In [6], we showed that several of the common properties of classes of algebras presented in the above sections are consequence of the cyclotomic condition. In particular, properties of the structure of the Auslander-Reiten quiver of the derived category Der(A).…”
Section: One-point Extensions Of Canonical Algebrasmentioning
confidence: 88%
See 4 more Smart Citations
“…In [6], we showed that several of the common properties of classes of algebras presented in the above sections are consequence of the cyclotomic condition. In particular, properties of the structure of the Auslander-Reiten quiver of the derived category Der(A).…”
Section: One-point Extensions Of Canonical Algebrasmentioning
confidence: 88%
“…In a recent paper [6] we show that always e(φ A ) ≥ n and equality is reached when A is of cyclotomic type, that is, χ A (T ) factorizes as product of cyclotomic polynomials (equivalently ρ A = 1 or M (φ A ) = 1). Many finite dimensional algebras are known to be of cyclotomic type: hereditary algebras of finite or tame representation type, canonical algebras, some extended canonical algebras and many others, see [17,18,23,6] and Section 2 for more examples. For algebras A not of cyclotomic type, important results concerning the growth of the iterated Auslander-Reiten translation τ s X, for X an A-module, s ∈ N, have been shown, see [8,7,21].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations